De lege ferenda Proposals Developed in German Criminal Law to Punish Company Executives Who Fail to Prevent Crimes Committed by Subordinates - Contreras Chaimovich, Lautaro Camilo (2025)
Commission by omission presents important difficulties as a mechanism to penalize corporate management bodies that violate their duties of organization, instruction, supervision or intervention. These difficulties are related to the legal requirements in terms of (quasi-)causality and intent. To overcome these obstacles, a sector of German criminal doctrine has proposed different alternatives de lege ferenda—in the form of criminal types different from those of improper omission—to punish the infringement of the aforementioned duties. The purpose of this article is to explain and critically assess these proposals.